IKLAN DAN HIPER-REALITAS PEREMPUAN - Wiryanti B.U., Sri (Institute of Research and Community Outreach - Petra Christian University, 2004)
Advertisment is a hiperrealistic reality discourse. Imaging in advertisement always related with aesthetic creativity%2C wich is subject to reality but not reality itself. Advertisement always image woman can be look more pretty%2C sexy woman look sexiest. Abstract in Bahasa Indonesia : Iklan merupakan wacana realitas yang hiperrealistik. Pencitraan dalam iklan tidak lepas dari kreativitas estetik%2C mengacu pada realitas tetapi bukan realitas itu sendiri. Dalam hal ini citra perempuan cantik dapat lebih cantik%2C perempuan seksi lebih seksi. reality%2C hipereality%2C image.